2009 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (IEEE transactions on audio, speech, and language processing, 2009)
Prospective authors are requested to submit new, unpublished manuscripts for inclusion in the upcoming event described in this call for papers.